KAJIAN PENINGKATAN KETERAMPILAN TENAGA KERJA - Hermansyah Masran (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2011)
The purpose of this study is to analyze the current employment situation in Palalawan Regency as well as estimates of future visits from the demand side and availability. Research locations covering 12 Districts as well as existing companies in Pelalawan District. Methods of data collection used are interviews, seeking and observation. They are analyzed by using SWOT (Strengths, Weaknesses, Opportunities, and Threats) and discrepancy analysis. The result of the study shows that during the period 2009 - 2013 population growth rate is at 4.46%, employment growth rates in the range of 4:30%, economic growth rates in the range of 5.50% and employment growth approximately 4.47%. The study recommends a policy of employment in the sector of economic, social, culture, territory, potential sectors of agriculture, plantation, fishery and animal husbandry, mining and energy, and the education sector.